2017
DOI: 10.1155/2017/8370106
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A Control in Meat Derivatives: Intraspecific Biocompetition betweenPenicillium nordicumStrains

Abstract: APenicillium nordicumstrain previously assessed for its atoxigenicity was tested against a toxigenic strain of the same species on salami, in order to assess its effectiveness as a biocontrol agent for OTA containment. Sixtysalamiwere inoculated with different combinations ofP. nordicumOTA−/OTA+ suspensions and ripened under controlled thermohygrometric conditions. After 7, 18, 29, and 40 days, both fungal counts and chemical analyses were carried out on casings. OTA was never found insalamiused as a control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…P. nordicum is a psychrotrophic fungi and widely distributed contaminant in various meat products [70][71][72][73][74]. It is considered an important OTA producer in dry-cured ham and dry-cured fermented sausage [24,28,70,[75][76][77][78]. The ability of P. nalgiovense, P. chrysogenum, P. olsonii, P. solitum and P. salamii to produce OTA in dry meat products has been reported in previous studies [50,79].…”
Section: Production Of Ota In Meat and Meat Productsmentioning
confidence: 84%
See 2 more Smart Citations
“…P. nordicum is a psychrotrophic fungi and widely distributed contaminant in various meat products [70][71][72][73][74]. It is considered an important OTA producer in dry-cured ham and dry-cured fermented sausage [24,28,70,[75][76][77][78]. The ability of P. nalgiovense, P. chrysogenum, P. olsonii, P. solitum and P. salamii to produce OTA in dry meat products has been reported in previous studies [50,79].…”
Section: Production Of Ota In Meat and Meat Productsmentioning
confidence: 84%
“…The occurrence of OTA in contaminated meat products may also be due to the growth of OTA-producing fungi in these products [26][27][28][29][30]94]. Surveys in ham-manufacturing plants revealed that OTA toxigenic strains of Aspergilli and Penicillia were present in the ripening rooms [98,189].…”
Section: Occurrence Of Ota In Pork Meat Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, both European and American regulations didn’t set an international legal limit of ochratoxin A in meat and meat products. Only Italy set the legal limit of ochratoxin A as 1 μg/kg meat [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…PgAFP-producing P. chrysogenum RP42C was also demonstrated to preserve ham from OTA occurrence, for up to 9 months, with respect to other mixtures of selected autochthonous non-toxigenic moulds [8]. An almost atoxigenic P. nordicum strain [84], was also shown to reduce OTA accumulation by 90% on salami when co-inoculated with a toxigenic P. nordicum strain. However, it should also be noted that commercial meat starter cultures of bacterial origin and autochthonous yeasts exert varying responses, sometimes stimulating growth and OTA production by A. westerdijkiae and P. nordicum in different meat-based media [85].…”
Section: Biocompetition Between Fungal Strains For Mycotoxins Risk Rementioning
confidence: 99%